TRANSPARANSI PENGELOLAAN DANA DESA DI DESA MELILIAN KECAMATAN GELUMBANG KABUPATEN MUARA ENIM - Umi Purwanti (MAP Program Pascasarjana Universitas Sjakhyakirti, 2021)
Transparency is one of the principles that can guarantee access or freedom for all people to obtain information about the administration and management carried out by the government. With the principle of transparency, it is hoped that the Melilian Village government, Gelumbang District, will manage the Village Fund transparently and involve the Village community. This study aims to describe the management of Village Funds and the mechanisms for managing Village Funds carried out by the Melilian Village Government, Gelumbang District, Muara Enim Regency. The method used in this research is descriptive qualitative method. Data collection techniques in this study include, observation, interviews and documentation. The results showed that the management of the Village Fund carried out by the Melilian Village government, Gelumbang District, was in accordance with the applicable laws and regulations and involved the community from the planning, implementation, administration, reporting and accountability stages to the delivery of development results. Based on the transparency indicator, it shows that there is availability of document accessibility as well as completeness, clarity and convenience for the public to access information as a whole with the installation of billboards and information boards at several points. This study concludes that Melilian Village, Gelumbang Subdistrict, has carried out the process of the Village Fund management mechanism in stages by involving several related elements including the people of Melilian Village, Gelumbang District.